Role of emotional intelligence within transactional - transformational leadership - Ferres, N.; Travaglione, Tony; O'Neill, Grant (Fort Hays State University, 2005)
This study explored the role of emotional intelligence (EI) within transactional-transformational leadership, and examined the impact of each leadership style on trust in leaders and trust in the organization. Results from 448 public-sector employees showed that leader EI was positively correlated with transformational leadership and transactional leadership. Transformational leadership and contingent-reward were both found to be significant positive influences on trust in immediate leader and trust in the organization, confirming expectations. In contradiction to the final hypotheses, transactional leadership also played a significant part in trust scores.